Producing Policy-relevant Science by Enhancing Robustness and Model Integration for the Assessment of Global Environmental Change. (January 2019) - Warren, R.F.; Edwards, N.R.; Babonneau, F.; Bacon, P.M.; Dietrich, J.P.; Ford, R.W.; Garthwaite, P.; Gerten, D.; Goswami, S.; Haurie, A.; Hiscock, K.; Holden, P.B.; et al.
Abstract: We use the flexible model coupling technology known as the bespoke framework generator to link established existing modules representing dynamics in the global economy (GEMINI_E3), the energy system (TIAM-WORLD), the global and regional climate system (MAGICC6, PLASIM-ENTS and ClimGEN), the agricultural system, the hydrological system and ecosystems (LPJmL), together in a single integrated assessment modelling (IAM) framework, building on the pre-existing framework of the Community Integrated Assessment System. Next, we demonstrate the application of the framework to produce policy-relevant scientific information. We use it to show that when using carbon price mechanisms to induce a transition from a high-carbon to a low-carbon economy, prices can be minimised if policy action is taken early, if burden sharing regimes are used, and if agriculture is intensified. Some of the coupled models have been made available for use at a secure and user-friendly web portal. Highlights: A flexible bespoke framework generator was used to couple software modules together. As in the Community Integrated Assessment System, alternative couplings were produced. Modules represent the energy system, climate, ecosystems, agriculture and hydrology. They were applied to simulate a transition from a high-carbon to a low-carbon economy. Associated carbon prices can be minimised by early action and burden sharing regimes.